2018
DOI: 10.22367/jem.2018.32.04
|View full text |Cite
|
Sign up to set email alerts
|

The Global Risk Landscape – its Shape, Tendencies,and Consequences for Management

Abstract: Aim/purpose -The main objectives of this article are to identify the major risks with a global dimension and to attempt to specify the potential consequences of their occurrence for organizational management. Design/methodology/approach -The article is based on an analysis of the literature on the subject and an analysis of the content of The Global Risk Reports published in the years 2013-2017, prepared within the scope of the World Economic Forum, and presenting the results of work performed by international… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 15 publications
0
6
0
1
Order By: Relevance
“…Apart from compulsory or regulatory requirements, it could be considered a way to mediate and moderate agency conflicts and information asymmetries (Cohen, Holder-Webb, Nath, & Wood, 2011;Voeller et al, 2013;Watts & Zimmerman, 2014). Similarly, Ismail et al (2008) conducted research in Malaysia, which confirmed that the presence of internal audit and its quality guarantee a positive influence and financial performance. This can happen because internal audits are aggressively driving their various resources to back the organization in improving their business performance, as supported by Warren et al (2011).…”
Section: Internal Audit Affects Firm Performancementioning
confidence: 85%
“…Apart from compulsory or regulatory requirements, it could be considered a way to mediate and moderate agency conflicts and information asymmetries (Cohen, Holder-Webb, Nath, & Wood, 2011;Voeller et al, 2013;Watts & Zimmerman, 2014). Similarly, Ismail et al (2008) conducted research in Malaysia, which confirmed that the presence of internal audit and its quality guarantee a positive influence and financial performance. This can happen because internal audits are aggressively driving their various resources to back the organization in improving their business performance, as supported by Warren et al (2011).…”
Section: Internal Audit Affects Firm Performancementioning
confidence: 85%
“…Dicho reporte destaca entre muchos otros, puesto que no solo aborda el riesgo geopolítico sino que ahonda también en los riesgos actuales más significativos a escala global, así como algunas tendencias en los mismos. Todo lo anterior, a fin de reconocer la influencia que todos estos riesgos ejercen en los procesos de gestión organizacional (Jedynak y Bąk, 2018).…”
Section: ¿Por Qué El Análisis Del Riesgo Geopolítico Dentro De Los Negocios Internacionales?unclassified
“…A necessary condition for the effectiveness of management processes in the conditions of risk is, above all, a good understanding of the risk itself, which is possible by identifying risk factors Such identification should be a continuous process. Updating identified risk factors in adapting to changes in the environment helps to develop adequate ways of responding to the occurring risk, and thus has a positive impact on the effectiveness of the risk management process (Jedynak and Bąk, 2018). These activities should lead to the creation of a risk profile, understood as a set of identified factors/phenomena assessed as having potentially undesirable effects on the operation of the system.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, as a result of the processes of continuing globalization, which is not indifferent to the nature of risk, 25 years later, the same author modified the concept of "risk society", henceforth using the term "global risk society" (Beck, 2012). For business entities, regardless of their size or sectoral affiliation, risk globalization means a change in the conditions for conducting business, transforming the management processes of these entities, which should ensure the ability to survive and develop in changed operating conditions (Jedynak and Bąk, 2018). Globalization also brings a number of technological changes, that are of particular importance for international enterprises, enterprises whose activities are related to technologies and innovations, as well as for enterprises whose activity is based on continuous contacts with contractors from other countries (Petricevic and Teece, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%